How to design bibliometric research: an overview and a framework proposal - Oğuzhan Öztürk; Rıdvan Kocaman; Dominik K. Kanbach (Review of Managerial Science, 2024)
Abstract Bibliometric analysis has recently become a popular and rigorous technique used for exploring and analyzing the literature in business and management. Prior studies principally focused on `how to do bibliometric analysis', presenting an overview of the bibliometric methodology along with various techniques and step-by-step guidelines that can be relied on to rigorously conduct bibliometric analysis. However, the current body of evidence is limited in its ability to provide practical knowledge that can enhance the design and performance of bibliometric research. This claim is supported even by the fact that relevant studies refer to their work as `bibliometric analysis' rather than `bibliometric research'. Accordingly, we endeavor to offer a more functional framework for researchers who wish to design/conduct bibliometric research on any field of research, especially business and management. To do this, we followed a twofold way. We first outlined the main stages and steps of typical bibliometric research. Then, we proposed a comprehensive framework for specifying how to design/conduct the research and under what headings the relevant stages (step-by-step) will be used and/or presented. Thus, the current paper is expected to be a useful source to gain insights into the available techniques and guide researchers in designing/conducting bibliometric research.
Additional information: M1;M19
Keywords: 330; Bibliometric research; Bibliometric analysis; Literature review; Bibliometric research design